MEMBANGUN NAGARI FOTOKOPI MELALUI KULIAH KERJA NYATA REVOLUSI MENTAL INDONESIA MELAYANI DI KABUPATEN TANAH DATAR - Helmizar Helmizar; Aulia Rahmi Putri; Ajie Syaputra (BULETIN ILMIAH NAGARI MEMBANGUN, 2018)
Nagari Atar is one of the viilage in Padang Ganting sub-district of Tanah Datar Regency which is located in a hilly geographical area. Nearly half of its people went migrating to other eities, provinces even countries to earn their living. Therefore “ Nagari Atar” is wellknown as “ Nagari Parantau” migrant village. Surprisingly , those migrants mostly earn their living as photo copy shop owners or managers, at least as photo copy shop keepers. Based on This fact Nagari Atar gets its famous name as “ Nagari foto kopi” photo copy village. With a splendid idea , people at Nagari Atar built up a statue which is called photo copy statue as a proud monument. It is located in front of the office of the Guardian Nagari . Since people of Nagari Atar mostly went migrating only few potentials can serve properly. Therefore this social service is aimed at helping the community to develop the existing potentials through the activities of lecturing on the real wish an Indonesian.